Pre-Service Teachers Reasons and Beliefs about Teaching as a Profession - Alshraideh, Mohamed Khaliefeh (EDUCARE, 2015)
ABSTRACT: Teaching is a main goal of teacher education students. Teacher education students must be well prepared in order to be ready for their future career as teachers. The study aimed at examining pre-service teachersâ reasons and beliefs about teaching in Umm-Alqura University as a profession. The study attempted to answer the following research questions: (1) What are the type of reasons that influenced the pre-service teachers decisions to become teachers?; (2) What are the types of beliefs that influenced the pre-service teachersâ decisions to become teachers?; (3) Is there statistical significant difference between pre-service teachersâ reasons and beliefs to become teachers?; (4) Is there statistical significant difference, Î± â¤ 0.05, on reasons that influenced the pre-service teachersâ decisions to become teachers?; and (5) Is there statistical significant difference, Î± â¤ 0.05, on beliefs that influenced the pre-service teachersâ decisions to become teachers? The participants were 321 male and female students enrolled in the fall semester of the academic year 2013 in Umm-Alqura University, in both the education and scientific colleges. About 187 participants were from the college of education and 134 participants were from the college of science. The data were collected by distributing three questionnaires. One for demographic characteristics, another one for the studentsâ reasons behind choosing teaching as a career, and a third one was for the studentsâ beliefs about choosing teaching as a career. Results showed significant differences between gender, major, and the interaction between them regarding their reasons and beliefs about teaching as a career. KEY WORDS: Reasons, beliefs, teaching, teacher education students, pre-service teachersâ reasons and beliefs, Umm-Alqura University, and teaching as a career.About the Author: Dr. Mohamed Khaliefeh Alshraideh is an Associate Professor at the Curriculum and Instruction Department, College of Education, Umm-Alqura University, Mecca, Saudi Arabia. For academic interests, the author can be contacted via e-mail at: shraideh@yahoo.comHow to cite this article? Alshraideh, Mohamed Khaliefeh. (2015). âPre-Service Teachers Reasons and Beliefs about Teaching as a Professionâ in EDUCARE: International Journal for Educational Studies, Vol.7(2) February, pp.111-122. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (November 21, 2014); Revised (December 29, 2014); and Published (February 28, 2015).